PROGRAM PELATIHAN DAN KINERJA PADA INDUSTRI PERBANKAN SYARIAH - Badawi Badawi; Wiwi Hartati; Harry Safari (JMB : Jurnal Manajemen dan Bisnis, 2018)
Problems regarding performance are problems that will always be faced by the management of the company, therefore management needs to know the factors that affect employee performance. Factors that can affect employee performance are training programs. This study aims to find out and analyze the influence of training programs that include training needs, training design and training evaluation on the performance of the Islamic banking sector in Cirebon Region. The method used in this research is field research to test hypothesis testing about the effect of training programs on performance in the Syarah breeding service sector in Cirebon. The unit of analysis in this study were individuals, namely Islamic bank employees in Cirebon, which numbered 50 employees. The analysis technique used is Path analysis. The results of this study indicate a training program on the dimensions of training design, on the job training and the type of training influencing employee performance in the Islamic banking services sector